Understanding inclusive playgrounds - Mohd Daniel, Mohd Idros; Puteri Fadzline, Muhamad Tamyez; Wan Zaiyana, Mohd Yusof; Hafizoah, Kassim; Muhammad Ashraf, Fauzi (Universiti Malaysia Sarawak, 2023)
Inclusive education has shown an increasing interest in teaching students with autism spectrum disorder (ASD) through playgrounds. This approach not only fosters the development of social skills but also enhances cognitive and emotional growth in learners. Although the playground's impact on the skills of ASD students has been acknowledged, some criticism stems from the lack of a precise conceptualisation. Recent studies have highlighted the significance of teaching through playgrounds in improving problem-solving abilities. While there is a growing body of research on hands-on learning through playgrounds, a challenge remains in tailoring the learning experience to accommodate individual differences among ASD learners. Detailed discussions on supporting personalised learning experiences and cognitive enhancement in the playground setting are lacking. This paper is a literature review and qualitative investigation to address these gaps. The main contributions are twofold: first, it offers a review of how the physical space of the playground design impacts the development of children with ASD, and second, it suggests several implications for future research based on extensive literature review and qualitative study.